Pengaruh Penambahan Tepung Mocaf dan Tepung Maggot Black Soldier Fly (BSF) Pada Pakan Pelet Terhadap Pertumbuhan Ikan Lele (Clarias sp.) - kiptiyah, mariatul; pamungkas, pictada putri; ernawati, ernawati (Lempuk: Jurnal Ilmu Kelautan dan Perikanan, 2022)
Catfish (Clarias sp) is one of the freshwater fishery commodities that has superior value compared to other freshwater fish species, which have relatively fast growth, strong survival, and adaptability to their habitat. Feed is an important factor in fish farming. Mocaf flour is processed cassava flour that has been fermented and produced cassava flour. Black Soldier Fly (BSF) maggot larvae are omnivores (eating everything) such as fruit waste, vegetable waste, food scraps, bones, and meat, to animals that have become carrion. This study aims to determine the effect of mocaf flour and BSF maggot flour on pellet feed on the growth of catfish (Clarias Sp.) and to determine the best formulation between mocaf flour and BSF maggot flour on the growth of catfish (Clarias Sp.). The method used in this study was Completely Randomized Design (CRD) with 3 treatments and repeated 3 times. The results of the feed will be tested with variance using ANOVA at a 95% confidence interval and further tested using the Tuckey test and the de Garmo effectiveness index. Results Mocaf flour gives a good effect when mixed with maggot flour. A good percentage of feed in a mixture of mocaf flour and maggot flour is found in P1 treatment, namely by mixing 25% mocaf flour + 75% maggot flour produces an efficient feed composition and is used to grow in length and weight of catfish.